WAKAF UANG SEBAGAI UPAYA PEMBERDAYAAN EKONOMI UMAT - Subaidi; Subyanto Subyanto; Mustofa Mustofa (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
Waqf is a potential source of funds that can be used as a tool to increase the economic welfare of the people. Waqf has helped Indonesia's overall development, both in the development of human resources and in the development of social resources. Apart from being a means to improve the economy and social welfare, cash waqf can also be used as a means to strengthen the bonds of brotherhood between the rich and the poor. Also, it can erode a sense of individuality and foster a sense of solidarity.